Advocacy Identifier Framework for Recognizing the Measurable Characters of Online Brand Advocate - Kichwarajarukul, Kanyapak; Mayakul, Theeraya; Borriraklert, Atthaves (Journal of Ecohumanism, 2024)
The rise of digital technology has shifted marketing power from companies to customers, enabling them to express opinions, share experiences, and support brands on online platforms. This phenomenon, known as online brand advocacy, represents a powerful form of customer influence; however, the specific characteristics of advocacy behavior remain unclear, posing challenges for marketers aiming to identify and engage brand advocates effectively. This research seeks to establish a framework for recognizing measurable traits of online brand advocates, based on a systematic literature review identifying three key domains: expression, engagement, and expenditure. Expression reflects customer satisfaction through ratings and reviews; engagement is shown by actions such as sharing reviews and contributing to the online community; and expenditure highlights purchasing patterns, including purchase frequency and average order value. An expert panel validated this framework using the Content Validity Index (CVI) and Cronbach’s alpha, confirming both its relevance and reliability. This framework provides a valuable tool for businesses, enabling them to analyze customer data, segment brand advocates, and leverage their support in the data-driven marketing landscape.